Investigations on the effects of superposition of X-radiations and the J-phenomenon - Gupta, Mohit Mohan Sen (The University of Edinburgh, 1928)
The present thesis contains an account of various experiments which were directed to the study of the phenomenon In the scattered X-radiation by the absorption methods. In these investigations, all the three different means of exciting X-ray tubes viz: (a) an induction coil (b) an influence machine and (c) a step-up transformer operated by A.c. primary current, were used successively, with the purpose of studying the phenomenon under a much wider range of conditions and in particular, of making a more direct investigation of the meaning of the critical factor, for it had previously been found1 that the details of the method of excitation was of considerable•importance in determining the degree of activity due to a complex beam of X-rays. A comparison of the results of the preliminary experiments using a gas tube excited by an intermittent high potential from an induction coil with those of similar experiments using a Coolidge tube excited by constant high potential from a plate machine led to an interesting conclusion. It was found that conditions favourable to exhibit J- discontinuities were more consistently obtained when a Coolidge tube excited by a plate machine was used, provided the procedure was to run the tube continuously throughout an experiment. Observations were then made with the aid of a shutter without interrupting the steady state attained by the tube. A series of experiments was then carried out on the effects of superposition of X-radiations (both when the superposition is effected in the ionisation chamber and only In the absorbing substance): using a plate machine and a Coolidge X-ray tube. The results of all these experiments are embodied in Part I of this thesis.

In a further investigation, a Coolidge X-ray tube excited by a step-up transformer, (primary A.c. current being obtained from the City supply at 230-250 volts) was employed. These investigations were made to study the nature of the modification produced in X-radiation by scattering from different substances and from scattering substances of various thicknesses. The method was to direct a primary beam of X-rays on to a scatterer of low atomic weight and to compare the radiation scattered in a direction at right angles to the incident beam, (producing an ionisation S in an ionisation chamber arranged to receive it) with the ionisation P produced by the direct beam which had passed through the scatterer. The ratio S/P was measured directly. Absorbing sheets of aluminium of equal thickness were then placed in the paths of both beams and the ratio S¹/P¹ was obtained. Observations were then taken with different voltages on the tube. A systematic examination was made of the scattered radiation from different scattering substances, e.g. paraffin wax and paper. The results led to the important discovery that the modification produced in X-radiation by j scattering from thin scatterers was illustrative of the J-phenomenon, but when thick scatterers were used, the modification produced was definitely of the nature demanded by Compton's hypothesis. In fact it was found possible to trace a gradual development from one type of results to the others, by simply varying the thickness of the scattering substances. The results of these experiments are given in Part II of this thesis. The result when coordinated with that of Prof. Barkla (Nature, May 28, 1927) throws much light on the relation between the two phenomena, one of which is in agreement with the classical theory, the other of which supports the quantum theory. It appears definitely to be the link connecting the results which have been taken to support the quantum theory and the classical theory of scattering.